2020
DOI: 10.1055/s-0040-1714933
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Angiogenesis in Multiple Myeloma by VEGF Immunoexpression and Microvessel Density

Abstract: Background Multiple myeloma (MM) is a plasma cell disorder characterized by monoclonal proliferation of plasma cells in bone marrow. Plasmablastic MM is a morphologic subset of MM, containing ≥2% plasmablasts of all plasma cells. Methods The study included 30 consecutively diagnosed patients of MM (6 plasmablastic, 24 nonplasmablastic) over a span of 2 years. Angiogenesis in MM was assessed by analysis of vascular endothelial growth factor (VEGF) immunoexpression by plasma cells and microvessel density (MVD) u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 15 publications
1
9
0
1
Order By: Relevance
“…This was consistent with Rana et al In the present study, it was revealed that MVD increased with immaturity of plasma cells. It was supported by Palta et al [8].…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…This was consistent with Rana et al In the present study, it was revealed that MVD increased with immaturity of plasma cells. It was supported by Palta et al [8].…”
Section: Discussionmentioning
confidence: 66%
“…Additional evidence indicates that angiogenesis in bone marrow corresponds with the production of neoplastic plasma cells and has a critical role in the course of disease [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple myeloma cells can bind to cellulose in the microenvironment and generate cell adhesion-mediated chemotherapeutic drug resistance. However, cytokines such as IL-6 and VEGF can induce the activation of a variety of signaling pathways and promote cell adhesion-mediated drug resistance, thus promoting the proliferation of multiple myeloma cells and inhibiting cell apoptosis [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another research found that most of the MM cases exhibited strong VEGF expression. Also, VEGF expression is positively correlated to MVD ( 138 ). VEGF and its type 2 receptor (VEGFR2) polymorphisms are related to the increased risk and aggressiveness in MM ( 139 ).…”
Section: The Yin and Yang Effects Of Non-cellular Components Associat...mentioning
confidence: 99%